Design and fabrication of multipurpose table kid - Tan, Choon Mong (2011)
The study of manufacturing was very important in order to carry out this project to ensure that the student understand on what are needs to do. This report present about design and fabricate a multipurpose, long-life span and lower cost table kid. The table kid is one classes of table which enable children to writing, reading, drawing and store their stationaries. In this project, concept is generated through research on existing product in order to improve its limitation. The material of steel and wood were using to fabricate this table kid. Mild-steel and galvanized iron was used to accomplish the factor of long life span. In other hand, the design of two surface tables were joined is enable factor of multi-user and also save space. SolidWorks Simulation Xpress software is using to do the stress and displacement analysis in order to study the maximum load of the multipurpose table kid can support. In the other hand, SolidWork Mass Estimation also is used to know the weight of the multipurpose table kid. Methods and process involve in this project include joining using MIG welding, making hole with drilling method, bending using profile bending machine and bending machine and also cutting using shearing machine.